Sitagliptin Treatment After Total Pancreatectomy With Islet Autotransplantation: A Randomized, Placebo‐Controlled Study. Issue 2 (26th August 2016) - Bellin, M. D.; Beilman, G. J.; Dunn, T. B.; Pruett, T. L.; Sutherland, D. E. R.; Chinnakotla, S.; Hodges, J. S.; Lane, A.; Ptacek, P.; Berry, K. L.; Hering, B. J.; Moran, A.
Abstract : Insulin independence after total pancreatectomy and islet autotransplant (TPIAT) for chronic pancreatitis is limited by a high rate of postprocedure beta cell apoptosis. Endogenous glucagon‐like peptide‐1 and glucose‐dependent insulinotropic peptide, which are increased by dipeptidyl peptidase 4 inhibitor therapy (sitagliptin) may protect against beta cell apoptosis. To determine the effect of sitagliptin after TPIAT, 83 adult TPIAT recipients were randomized to receive sitagliptin (n = 54) or placebo (n = 29) for 12 months after TPIAT. At 12 and 18 months after TPIAT, participants were assessed for insulin independence; metabolic testing was performed with mixed meal tolerance testing and frequent sample intravenous glucose tolerance testing. Insulin independence did not differ between the sitagliptin and placebo groups at 12 months (42% vs. 45%, p = 0.82) or 18 months (36% vs. 44%, p = 0.48). At 12 months, insulin dose was 9.0 (standard error 1.7) units/day and 7.9 (2.2) units/day in the sitagliptin and placebo groups, respectively (p = 0.67) and at 18 months 10.3 (1.9) and 7.1 (2.6) units/day, respectively (p = 0.32). Hemoglobin A1c levels and insulin secretory measures were similar in the two groups, as were adverse events. In conclusion, sitagliptin could be safely administered but did not improve metabolic outcomes after TPIAT. Abstract : In this randomized, placebo‐controlled trial, treatment with once‐daily sitagliptin for 1 year after total pancreatectomy with islet autotransplant did not improve diabetes outcomes at 12 or 18 months posttransplant.